Anticancer effect of crizotinib on osteosarcoma cells by targeting c-Met signaling pathway: Crizotinib targets c-Met in osteosarcoma - Jia, Tao; Cai, Mengmeng; Wang, Zengkun; Chen, Tianxin (Cellular and Molecular Biology, 2023)
C-Met receptor and its ligand hepatocyte growth factor (HGF) are overexpressed in a variety of osteosarcoma cell lines and osteosarcoma pathological samples. It is suggested that c-Met/HGF plays an important role in the development of osteosarcoma. This study aimed to explore the anticancer effect of the c-Met-targeted drug crizotinib on osteosarcoma (OS) cells. The effects of crizotinib on the proliferation of osteosarcoma cells (SaOS2, MG-63 and MNNG) at different concentrations were detected by CCK8. Human osteosarcoma cell line MG-63 was used as an in vitro model to evaluate the effects of 2.5 μM crizotinib, 5.0 μM crizotinib and DMSO on cell apoptosis, cell cycle, migration and invasion. The expression of the c-Met signaling pathway in osteosarcoma cells was detected by western blot. The results showed that crizotinib inhibited the proliferation of cell lines in a concentration-dependent manner. Crizotinib significantly increased the number of apoptotic cells compared with the control group. Compared with the control group, crizotinib increased G0/G1 phase cells and decreased S phase cells. Compared with the control group, crizotinib inhibited the migration and invasion of osteosarcoma cells and decreased the expression of c-Met/Gab1/STAT5. This study will provide a promising therapeutic target and theoretical basis for the clinical application of crizotinib in osteosarcoma.